Extreme light fields and their interaction with matter : Interference effects in the formation of the light bullet spectrum under axicon focusing. (16th April 2020) - Zaloznaya, E D; Kompanets, V O; Chekalin, S V; Dormidonov, A E; Kandidov, V P
Abstract: Specific features of the anti-Stokes band of the light bullet supercontinuum spectrum under filamentation of 1900-nm femtosecond pulses, focused by an axicon in fused silica and calcium fluoride, have been experimentally, numerically, and analytically investigated. It is found that the formation of two or more light bullets in a filament leads to modulation of spectral components' intensity. The oscillation period of spectral components, defined as the wavelength interval between adjacent intensity minima, decreases with decreasing their wavelength. On a logarithmic scale, the relative change in the oscillation period in the spectrum is proportional to the spectral component wavelength and is independent of the pulse energy and the position of the light bullet formation region in the filament. It is established that the modulation in the spectrum is due to the interference of the broadband supercontinuum emitted by light bullets, and its period decreases with increasing interval between them.